Green Marketing Exploration on Customer Retention in Improving Business Performance with Tacit Entrepreneurship Knowledge as Moderator - Anggraeni, Fadjar Setiyo (Journal of Digital Marketing and Halal Industry, 2020)
Global warming is a central issue, so it needs strategic steps for organizations or companies to find solutions because it threatens the future. This article aims to provide an overview of the importance of research on the role of green marketing and customer retention in improving business performance, using the factor of tacit entrepreneurial knowledge as a moderating variable. This research is qualitative, using a library research approach. The results obtained six preparations: First, the more effective the implementation of green marketing by the organization, the more it will improve customer retention patterns. The second proposition, the more effective green marketing is, the more business performance will be—the third proposition, the stronger the customer retention, the stronger the effect on improving organizational performance. The fourth proposition, the higher tacit knowledge about entrepreneurship possessed by organizations and individuals followed up intensively through interaction with customers, the customer resistance will increase, and the higher tacit knowledge owned by organizations and individuals in it, the more effective it will be. Green marketing. The fifth proposition, the higher the organization's tacit knowledge and the individuals in it, the higher the organizational performance will be.